Reconciling biodiversity conservation and food security: scientific challenges for a new agriculture - Brussaard, Lijbert; Caron, P.; Campbell, Bruce M.; Lipper, Leslie; Mainka, S; Rabbinge, Rudy; Babin, D.; Pulleman, Mirjam Margreet (Elsevier, 2010)
Production ecology and conservation biology have long focused on providing the knowledge base for intensive food production and biodiversity conservation, respectively. With increasing global food insecurity and continuing biodiversity decline, we show that the largely separate development of these fields is counterproductive. Scenario analyses suggest that feeding the world is possible without further encroachment of agriculture into natural ecosystems. Without ignoring the necessary demographic, socio-economic, institutional and governance requirements, we make the case for a science that develops the best ecological means to produce food in a way that has substantially less negative effects on biodiversity and associated ecosystem services and, indeed, should be able to contribute to their persistence and enhancement. Recent developments in trait-based ecology should soon make it possible to adapt and (re-)design agroecosystems to meet both goals of biodiversity conservation and food security. However, there are real tensions between, on the one hand, the opportunity costs of biodiversity conservation (for direct use and for conversion to agriculture) and on the other hand, the ecosystem service values and option values associated with biodiversity. We elaborate the management of plant genetic resources as a metaphor of the tensions between such values of biodiversity and ecosystem services in general. We conclude that significant changes in policies, institutions and practices are necessary to make advances in ecology work for reconciling biodiversity conservation and food security.